Development of a measure of the patient-provider relationship in antenatal care and its importance in PMTCT. - Barry, Oliver M; Bergh, Anne-Marie; Makin, Jennifer D; Etsane, Elsie; Kershaw, Trace S; Forsyth, Brian W C (AIDS care, 2012)
The prevention of mother-to-child HIV transmission (PMTCT) is a complex challenge in heavily affected and resource-limited settings such as South Africa. Management of PMTCT requires a cascade of interventions that need to be addressed to effectively decrease the risk of HIV transmission to infants. This PMTCT cascade includes incremental components that can be shaped and influenced by the patient-provider relationship. The relationship that a pregnant woman has with her care providers may possibly affect decisions that she makes concerning her antenatal care and may, in turn, influence the quality of the care provided. A patient-provider relationship scale (PPRS) was developed in Pretoria, South Africa with two aims: first, to quantify the patient-provider relationship in an antenatal population in a resource-limited setting and provide preliminary evidence of its reliability and validity; and second, to determine whether the patient-provider relationship has an effect on PMTCT. The instrument was administrated in a cross-sectional pilot study to a group of women at discharge after delivery (n=192) at two major hospitals in South West Tshwane. Statistical analysis of the instrument showed high reliability (α=0.91) and preliminary evidence of its validity including significant associations with participants' attitudes regarding the functioning of the clinics and a single statement (the clinic staff "know me as a person," R=0.47, p<0.001) that has been shown previously to have a significant association with adherence to antiretroviral treatment. For HIV-positive participants, the PPRS was significantly associated with statements related to important components of the PMTCT cascade. In addition, those with substantially inadequate antenatal care (≤2 visits) and those who did not initiate highly active antiretroviral therapy, although eligible, had significantly poorer PPRS scores. The PPRS is a potentially useful, context-appropriate instrument that could have an important role in future research focused on improving PMTCT and decreasing the risk of HIV infection in children.
Keywords: Adult; Anti-HIV Agents; Counseling; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; HIV Seropositivity; Humans; Infectious Disease Transmission, Vertical; Maternal Health Services; Mothers; Patient Education as Topic; Pilot Projects; Pregnancy; Pregnancy Complications, Infectious; Prenatal Care; Professional-Patient Relations; Program Evaluation; Quality of Health Care; South Africa